Decision Support System Using the Multi-Objective Optimization Based on Ratio Analysis (MOORA) Method to Determine the World of Work Partners Competency Test at SMK Karnas Sindangwangi - Muhsidi, Adi Muhamad; Kosim, Kosim; Rifa Aksar, Fadila (MASI Mandiri Edukasi, 2024)
Vocational High Schools (SMK) are designed to prepare students to enter the world of work or business with a focus on specific skills. The Skills Competency Test (UKK) is an effort by the government to ensure the quality of education in SMK. SMK Karya Nasional Sindangwangi organises UKK Mandiri using standardised instruments from the government and involving workplace partners. Currently, the selection of workforce partners in this school still needs to be done conventionally, making it challenging to determine relevant partners. This research aims to build a Decision Support System (DSS) to determine the optimal workplace partners for implementing UKK at SMK using the Multi-Objective Optimization based on Ratio Analysis (MOORA) method. This method calculates the final value converted into a matrix to obtain a value index (Yi) used for partner ranking. The alternative with the highest value from the benefit and cost criteria calculation is considered the best. The results showed PT Telkom Indonesia (Persero) as the best partner with a weight value of 0.3235, followed by PT Len Industri (Persero) with a value of 0.2656, PT Akur Pratama (Yogya Group) 0.2240, PT Arta Flash Sintesa Nusantara 0.1844, PT Seong Sin Tech 0.1553, and PT Indosat Ooredoo Tbk 0.1365. This research provides recommendations for optimal workforce partners for vocational schools.